Hyperacute stent placement in acute cervical internal carotid artery occlusions: the potential role of magnetic resonance imaging. (17th August 2009) - Jha, R M; Hochberg, L R; Hakimelahi, R; Hirsch, J A; González, R G; Yoo, A J
Abstract : Cervical internal carotid artery (ICA) occlusions causing acute ischemic stroke have extremely poor outcomes without rapid re-establishment of cerebral perfusion. Given the high risk for early recurrent stroke, carotid stenting at the time of intra-arterial therapy may be crucial to improving outcomes. To our knowledge, there are only two prior case series that address intra-arterial reperfusion therapy and stent placement within six hours of stroke onset (the hyperacute period). We present two cases to further support the feasibility of this intervention in the hyperacute period, and report the potential utility of MRI in identifying patients most likely to benefit from this procedure.